Investigation on false alarm for ultrasonic sensors / Nizammudin Jasnie - Jasnie, Nizammudin (2019)
The HC-SR04 was used as a basis for the study of parking sensors since they are both ultrasound sensor that applies the use of ultrasound to detect obstacles. The schematics of the HC-SR04 was studied and based on previous research the schematics were reversed, drawn and modified or added some form of small improvements to tackle the problems of false echoes that cause the sensor to detect obstacles which does is not desired or 0 returns where the sensor is unable to receive the reflected waves of its transmission when faced with an obstacle made up of soft material particularly that absorbs ultrasound waves. A new circuit was built based on the HC-SR04 schematics with significant alterations and the coding of the new circuit is slightly altered to obtain better signal results compared to the HC-SR04. The findings revealed that the circuit revealed some changes to the experimental set up for the alarm problem. The designed circuit could transmit ultrasound signals properly however its receiver configuration could not properly receive the desired reflected ultrasound signal. The problems with the receiver could be attributed to its configuration, temperature of surroundings and other noises inaudible to the human car.